Ahmadiyya Sheikh Marouf al-Nawdahi and its influence on the Kurdish language - the Sulaymaniyah dialect in the nineteenth century - عزيز, د. صلاح محمد (Sulaimani Journal for Humanities, 2024)
Muhammad Maruf ibn Mustafa al-Nawdahi, known as Sheikh Maruf al-Nawdahi (1166-1254 AH/1753-1838 CE), was a prominent religious scholar, teacher of Islamic sciences, and sheikh of the Qadiriyya Sufi order in Sulaymaniyah. He resided in Qalajolan during the reign of the Babi dynasty, later moving to the city of Sulaymaniyah, which was founded by the Babi government around 1200 AH/1785 CE. Sheikh Maruf al-Nawdahi was renowned for his skill in composing Arabic poetry, a talent he used to elucidate various aspects of Islamic worship, his opinions, philosophical concepts, and other topics. His literary contributions included the authorship of 55 works, most notably "Al-Ahmadiyya," the first Arabic-Kurdish dictionary in the region. Sheikh Maruf al-Nawdahi's literary endeavors, alongside those of classical poets of the early 19th century, played a pivotal role in establishing Sulaymaniyah as a significant center of Kurdish culture and literature. This literary renown has endured through the years and continues to distinguish Sulaimaniyah from other Kurdish cities to the present day. The current research focuses on three main questions about the Ahmadiyya: (a) the reasons behind its composition and timing, (b) its significance in understanding the cultural milieu of Sulaimaniyah during its formative period, and (c) its influence on the Kurdish language, including vocabulary and writing styles. To answer these questions, the researcher relied heavily on available copies of the Ahmadiyya, employing a critical analytical approach. The Ahmadiyya comprises a total of 1,184 Arabic words translated into Kurdish. By using critical analysis of these translated words, the researcher sheds light on the "common language" of Sulaimaniyah at that time and the Ahmadiyya's ability to preserve Kurdish words and spellings for over a century. The researcher also proposes new interpretations regarding the reasons for the Ahmadiyya's composition and the year of its creation. The researcher calls for a new method of reading manuscripts through critical analysis, as this is more accurate in understanding the manuscript and the logical reasoning of the author’s temporal-spatial culture.
Keywords: Sheikh Marouf AlNoudhi; AlAhmadiyya; Kurdish words and their spelling in the nineteenth and twentieth centuries